EU foreign policy through the lens of practice theory: A different approach to the European External Action Service. (September 2015) - Lequesne, Christian
There is a proliferation of works on the new European External Action Service (EEAS). Most of these approach the EEAS through a rationalist framework, assessing how a new institution can solve long-term questions of EU foreign policy-making to ensure consistency and coherence while reducing transaction costs between actors (both supranational and national) in a multilevel governance structure. This paper takes a different direction. Using 30 interviews with officials from the EEAS, the European Commission, and national ministries of foreign affairs, conducted between 2010 and 2013, it shows how the study of practice aids understanding of the nature of the EEAS. As a new institution, the EEAS lends itself particularly well to practice-based study because new institutions must develop new practices. The first section of the article defines the notion of practice and shows the importance of historicizing the struggles around practices in understanding the creation of the EEAS. The second section demonstrates how agents' practices shape professional cultures within the EEAS. The third section highlights the relationship between practices and rule-making. Going over the EEAS as a case study, the conclusion focuses on the importance of analysing actors' practices for understanding the current evolution of diplomacy and international relations in general.